Hodnocení stavebního projektu z hlediska celoživotních nákladů - Foitlová, Lucie (Vysoké učení technické v Brně. Fakulta stavební, 2018)
Teoretická část se v úvodu zabývá hodnocením efektivnosti projektu, dále především informacemi o jednotlivých etapách životního cyklu stavby, opotřebováním staveb, životnostmi prvků a celoživotními náklady stavby, které zajímají především investora. Závěrem jsou zmíněny odpady a emise. Práce je doplněna případovou studií rodinného domu, kde jsou řešeny celoživotní náklady cyklu stavby.

The theoretical part deals at the beginning with evaluation of effectiveness of the project, as well as with the information about individual stages of the life cycle of the building, wear and tear of the buildings, lifetime of the elements and whole life costs of the building that are of particular interest to the investor. In conclusion, there are mentioned wastes and emissions. The thesis is completed by a case study of the family house where the whole life costs of the building life cycle are solved.
Evaluation of Construction Project from aspect of Whole Life Costs
Keywords: Stavba; cyklus stavby; životnost; opotřebení; náklady; provozní náklady; etapy životního cyklu; investiční fáze; materiálové vstupy; odpady; energie; celoživotní náklady stavby.; Building; building life cycle; lifetime; wear and tear; costs; operating costs; stages of the life cycle; investment phase; material inputs; wastes; energies; whole life costs of building.